2009
DOI: 10.1111/j.1475-6811.2009.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment avoidance and commitment aversion: A script for relationship failure

Abstract: Do avoidantly attached individuals, with fears of closeness and dependency, expect their relationships to fail? Moreover, do they expect specific events that will lead to failure? Canadian students outlined their expectations for a new romantic relationship by ordering a series of dating events using a card sorting procedure. Avoidance was associated with both expectations of relationship failure and commitment aversion (the absence of positive commitment‐enhancing events and presence of negative commitment‐un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 48 publications
3
42
0
5
Order By: Relevance
“…Avoidant individuals are more likely to be distrusting and less intimacy-seeking than secure individuals, and are less likely to commit in their relationships (Birnie et al 2009). Highly avoidant individuals have a greater tendency to evade intimacy, show more discomfort with emotional closeness, and seek a higher level of self-sufficiency than do non-avoidant individuals (Bartholomew and Horowitz 1991); they appear to be less dedicated to the romantic partner and/or the relationship (personal commitment), which in turn negatively affects their relationship satisfaction through decreased pro-relationship behaviors, such as forgiveness and accommodation (e.g., Finkel et al 2002;Wieselquist et al 1999).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Avoidant individuals are more likely to be distrusting and less intimacy-seeking than secure individuals, and are less likely to commit in their relationships (Birnie et al 2009). Highly avoidant individuals have a greater tendency to evade intimacy, show more discomfort with emotional closeness, and seek a higher level of self-sufficiency than do non-avoidant individuals (Bartholomew and Horowitz 1991); they appear to be less dedicated to the romantic partner and/or the relationship (personal commitment), which in turn negatively affects their relationship satisfaction through decreased pro-relationship behaviors, such as forgiveness and accommodation (e.g., Finkel et al 2002;Wieselquist et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Birnie et al (2009) found that attachment avoidance was associated with commitment aversion. Avoidantly attached individuals tend to reject intimacy or closeness, and protect themselves from disappointments and rejection by others, maintaining a sense of independence and invulnerability (Feeney and Noller 1990;Hazan and Shaver 1987;Pistole and Vocaturo 1999).…”
Section: Commitment Attachment and Relationship Satisfactionmentioning
confidence: 97%
“…Explicitly, higher attachment avoidance, which was shown to be related with a decreased ability to either appreciate or acknowledge the positive aspects of one's romantic relationship, was in turn linked with lower couple satisfaction. According to Birnie, McClure, Lydon, and Holmberg (2009), avoidantly attached individuals often enter romantic relationships with negative partner and relational expectations that undermine their level of commitment. Given their expectation of negative events and anticipation of few positive events, avoidantly attached individuals often foresee their relationship as being prone to inevitably fail (Birnie et al, 2009).…”
Section: Mediating Role Of Commitment Goalsmentioning
confidence: 98%
“…According to Birnie, McClure, Lydon, and Holmberg (2009), avoidantly attached individuals often enter romantic relationships with negative partner and relational expectations that undermine their level of commitment. Given their expectation of negative events and anticipation of few positive events, avoidantly attached individuals often foresee their relationship as being prone to inevitably fail (Birnie et al, 2009). Perhaps these scripts, combined with a limited ability to acknowledge the positive aspects of their relationship (i.e., approach commitment goals), might not only explain why avoidant individuals are more likely to be discontent with their relationship (e.g., Feeney, 1999), but correspondingly, their tendency to demonstrate lower levels of general romantic commitment (Pistole et al, 1995).…”
Section: Mediating Role Of Commitment Goalsmentioning
confidence: 98%
“…Avoidant attachment patterns have been consistently associated with lower levels of commitment, which may be seen as a threat to the high need for autonomy associated with avoidant attachment (Birnie, McClure, Lydon, & Holmberg, 2009;Etcheverry, Le, Wu, & Wei, 2013;Hadden et al, 2014). The relationship between anxious attachment patterns and commitment seems to be more complex.…”
Section: Relationship Commitmentmentioning
confidence: 99%